PENGARUH MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN EDUCAPLAY TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR PADA SISWA KELAS III SDIT AL IMAM ASY-SYAFI’I NGAWI - Nadila Dyah Purnama Sari; Nofita Lestariningsih; Aulia Fajar Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the low mathematics learning outcomes of third-grade students on plane geometry material at SDIT Al Imam Asy-Syafi’i Ngawi, which are influenced by teacher-centered learning and limited use of interactive media. The purpose of this research is to determine the effect of the Project Based Learning (PjBL) model assisted by Educaplay on students’ learning outcomes. This study employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The sample consisted of 40 students divided into an experimental class and a control class. Data were collected through multiple-choice tests administered as pretest and posttest. The data analysis techniques included validity and reliability tests, normality and homogeneity tests, as well as hypothesis testing using paired sample t-test and independent sample t-test. The results showed that the average score of the experimental class increased significantly from pretest to posttest compared to the control class. This indicates that the application of the PjBL model assisted by Educaplay has a positive and significant effect on students’ mathematics learning outcomes, particularly in plane geometry material. Therefore, this model can be used as an effective and innovative learning alternative to improve student engagement and achievement.